2020
DOI: 10.1177/1550147720971504
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised learning trajectory anomaly detection algorithm based on deep representation

Abstract: Without ground-truth data, trajectory anomaly detection is a hard work and the result lacks of interpretability. Moreover, in most current methods, trajectories are represented by geometric features or their low-dimensional linear combination, and some hidden features and high-dimensional combined features cannot be found efficiently. Meanwhile, traditional methods still cannot get rid of the limitation of space attributes. Therefore, a novel trajectory anomaly detection algorithm is present in this article. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Given the labor-intensive process of labeling trajectories, a growing number of researchers have turned their attention towards exploring unsupervised learning methods [33]- [35]. These methods aim to learn patterns and detect outlier trajectories without the demands for pre-labeled data.…”
Section: B Learning-based Methodsmentioning
confidence: 99%
“…Given the labor-intensive process of labeling trajectories, a growing number of researchers have turned their attention towards exploring unsupervised learning methods [33]- [35]. These methods aim to learn patterns and detect outlier trajectories without the demands for pre-labeled data.…”
Section: B Learning-based Methodsmentioning
confidence: 99%
“…In [18] investigated the use of an interactive IoT cloud deep learning model to develop a personalized learning system for university students. The authors found that the model was effective in identifying individual learning needs and could be used to develop personalized learning resources that improved learning outcomes.…”
Section: Related Workmentioning
confidence: 99%
“…In this context, FDIA detection is treated as a supervised binary classification problem. Based on the research work done in [14] the SVM is more efficient than CNN and KNN in anomaly detection with 91.29% of precision. Moreover, the SVM is a popular practice for training a decision boundary that divides data into several classes.as shown in Fig.…”
Section: Proposed Modelmentioning
confidence: 99%